COMPARATIVE LOCAL GOVERNMENT RESPONSE TO COVID-19 IN DIFFERENT COUNTRIES: CASE IN GAMBIA AND INDONESIA - Jonga, Modou; Fauzi, Fadhli Zul (Jurnal Politik Pemerintahan Dharma Praja, 2022)
This study aims to evaluate the performance of two different local governments in two different nations using decentralization and policy implementation theories. It will also provide a general overview of the situation in these two nations at the time that Covid-19 began to spread. Using a comparative case study (CCS), this study compares local government response to Covid-19 in Gambia and Indonesia. In this study, the pandemic Covid-19 was given the same effect in each country but produced different results depending on government activities in each country. When the first Covid-19 cases appear in their countries, Gambia and Indonesia face a similar problem, but they also have a similar strategy for dealing with this pandemic outbreak. The Gambian government provides food, personal protective equipment (PPE), and essential sanitary items, as have several local governments in Indonesia. Gambia and Indonesia also establish a task force (both central and local government) to control virus spread, which becomes a key action in both countries' management of the Covid-19 outbreak. This research find that the role of local government in translating policy from the central government becomes critical to a region's success. A country's central government must not only maintain good performance in areas where it already excels, but also provide education and strong attention to local governments that are still struggling in order for them to improve their performance.